Beyond four decades of Elaeidobius kamerunicus Faust (Coleoptera: Curculionidae) in the Malaysian oil palm industry: a review - Zulkefli, Muhamad Haziq Hadif; Jamian, Syari; Adam, Nur Azura; Jalinas, Johari; Mohamad, Saharul Abillah; Mohd Masri, Mohamed Mazmira (Cambridge University Press, 2021)
Oil palm (Elaeis guineensis Jacq) is an economically important crop in South-east Asia, especially in Malaysia and Indonesia. In Malaysia, oil palm is the most profitable commodity in the agriculture sector. The future of oil palm lies in obtaining a higher yield that is aligned and directed towards achieving the Sustainable Development Goals (SDG) by 2030. Elaeidobius kamerunicus was introduced into Malaysia during the late 1980s to boost the production of oil palm fruit bunches. Almost 40 years since the introduction of E. kamerunicus, significant improvements have been witnessed in the increase of oil palm yield. Nevertheless, the current concern in the oil palm sector is regarding the decreasing of fruit set that may be affected by E. kamerunicus. The weevil population plays a crucial factor in the pollination of oil palm. Several factors had been reported to reduce the weevil population such as natural enemies, interaction with local insects, pesticides, climate and male inflorescence. These factors have been addressed in this article based on various studies conducted since the first investigation in Cameroon by Syed in 1977. The role of the pollinator in terms of its biology, behaviour and pollination mechanism is also described in this article, together with the population management of the weevils. This review article will provide a summary of the current state of Elaeidobius kamerunicus in Malaysia and other neighbouring oil palm-producing countries.